Giant fennel (Ferula communis L) intoxication in goats in Tunisia. Issue 4 (30th December 2018) - Lahmar, Rym; Mahjoub, Tarek; Fourel, Isabelle; Gault, Gilbert; Grancher, Denis
Abstract : Giant fennel ( Ferula communis L) toxicity has been commonly reported in different species, especially sheep, cattle, pig, horse and human but not in goat. A herd of 30 Damascus goats grazed during two days an area where F communis was very abundant. One week later, most animals presented clinical signs with locomotor disorders, anorexia and fever. Diagnosis of the intoxication was based on haematological parameters, toxicology research, necropsy and botanical investigation. Two goats survived following a treatment with vitamin K1 . A total of 13 animals died of which most were young. The present study is the first report providing information about F communis intoxication in goat.